Successful renal denervation decreases the platelet activation status in hypertensive patients. Issue 1 (4th February 2019) - Zaldivia, Maria T K; Hering, Dagmara; Marusic, Petra; Sata, Yusuke; Lee, Rebecca; Esler, Murray D; Htun, Nay M; Duval, Jacqueline; Hammond, Louise; Flierl, Ulrike; Wang, Xiaowei; Drummond, Grant R; et al.
Abstract: Aims: To determine whether renal denervation (RDN) in hypertensive patients affects the platelet activation status. Methods and results: We investigated the effect of RDN on the platelet activation status in 41 hypertensive patients undergoing RDN. Ambulatory blood pressure (BP), plasma sympathetic neurotransmitter Neuropeptide Y, and platelet activation markers were measured at baseline, at 3 months, and 6 months after RDN. RDN significantly decreased BP at 3 months (150.6 ± 11.3/80.9 ± 11.4 mmHg to 144.7 ± 12.0/77.1 ± 11.1 mmHg; P  < 0.01) and at 6 months (144.3 ± 13.8/78.3 ± 11.1 mmHg; P  < 0.01). Plasma levels of the sympathetic neurotransmitter Neuropeptide Y, an indicator of sympathetic nerve activity, were significantly decreased at 3 months (0.29 ± 0.11 ng/mL to 0.23 ± 0.11 ng/mL; P  < 0.0001) and at 6 months (0.22 ± 0.12 ng/mL; P  < 0.001) after RDN. This was associated with a reduction in platelet membrane P-selectin expression (3 months, P  < 0.05; 6 months, P  < 0.05), soluble P-selectin (6 months, P  < 0.05), circulating numbers of platelet-derived extracellular vesicles (EVs) (3 months, P  < 0.001; 6 months, P  < 0.01), and phosphatidylserine expressing EVs (3 months, P  < 0.001; 6 months, P  < 0.0001), indicative of a reduction in platelet activation status and procoagulant activity. Only patients who responded to RDN with a BP reduction showed inhibition of P-selectin expression at 3 months ( P  < 0.05) and 6 months ( P  < 0.05) as well as reduction of glycoprotein IIb/IIIa activation at 3 months ( P  < 0.05). Notably, 13 patients who took aspirin did not show significant reduction in platelet P-selectin expression following RDN. Conclusion: Our results imply a connection between the sympathetic nervous system and the platelet activation status and provide a potential mechanistic explanation by which RDN can have favourable effects towards reducing cardiovascular complications.